Flood Control Projects in the Philippines: A Historical Overview - Rinen, Richard Martin E.; Maki, Norio (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 8, 2022)
Floods have been a natural occurrence in the Philippines since the pre-Hispanic time because most settlements are in very close proximity to bodies of water. These floods often result in calamities that are aggravated by the uncontrolled urbanization which brings about even bigger problems. In order to mitigate the effects of flooding, especially in highly urbanized areas, different flood control projects have been undertaken by the Philippine government. But, despite these efforts, the problem persists and continues to threaten the growing population especially with climate change. This paper looked into different projects in combating flooding from the Hispanic period to the present. This is done by looking into flood control projects through the archives of the Bureau of Public Works (Department of Public Works and Highways) and other literature and categorizing them as risk reduction strategy or risk avoidance strategy. As a result, it can be noted that in the past, the placement of towns and villages and even the design of houses and buildings took into consideration flooding and other natural phenomena in their location and design, an effective risk avoidance strategy as in the case of the relocation of San Juan in Batangas. However, with the establishment of the Bureau of Public Works flood control projects focused mainly on costly structural solutions or risk reduction strategies as in the case of the Manggahan Floodway. Failure to finish and/or maintain these projects render them ineffective just like what happened during Typhoon Ondoy. Therefore, the most effective solutions in mitigating the effects of flooding are mostly non-structural in nature, however, there are situations where structural solutions are inevitable and therefore a combination of strategies with focus more on risk avoidance strategies should be considered. Keywords: disaster, disaster preparedness, risk avoidance, flood control, risk reduction